Interspecific hybridization in the genus Manihot progress and prospects - Asiedu, Robert; Hahn, S.K.; Bai, K.V.; Dixon, A. (International Society for Horticultural Science, 1994)
Most cassava (Manihot esculenta Crantz) improvement programs depend on the range of variability available within the cultigen for breeding varieties adapted to target environments. Efforts by some programs to introduce additional variability from wild Manihot species into cassava have led to improved diseases and pest resistance as well as higher ploidy levels. They have also provided insights into the evolution of the genus. Much remains to be investigated. This paper reviews the progress from the exploitation of the wild Manihot species for cassava improvement including data from the cassava breeding unit at IITA.